Position of leading corporations: empirical evidence from Russian economy - Yusupova, Almira (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The paper deals with the analysis of the role and ranking positions of leading corporations. Basic approach of industrial economics is used as the starting point of the analysis. Special coefficients of “sustainability” and “stability” of leadership, indicating companies’ positions, are proposed to describe firms’ market power. Empirical part is based on data provided by national rating agency Expert Ra for a long-term period from 2000 to 2011. Comparison of national and regional markets enabled us to find out that generally the positions of Russian leading corporations are stable and sustainable. Market power of leading companies is rather significant, therefore at the national level, competition could hardly be intensive. More competitive structures are developed at regional level. Regional markets demonstrated more rapid response to crisis. At the same time, expansion of national and transnational corporations has great influence on regional markets’ structures.